Retinal vasculature fractal dimension measures vessel density - Ab Hamid, Fadilah; Che Azemin, Mohd Zulfaezal; Salam, Adzura; Aminuddin, Amilia; Mohd Daud, Norsyazwani; Zahari, Ilyanoon (Taylor and Francis Ltd, 2016)
Purpose: The goal of this study was to provide the empirical evidence of fractal dimension as an indirect measure of retinal vasculature density. Materials and methods: Two hundred retinal samples of right eye [57.0% females (n = 114) and 43.0% males (n = 86)] were selected from baseline visit. A custom-written software was used for vessel segmentation. Vessel segmentation is the process of transforming two-dimensional color images into binary images (i.e. black and white pixels). The circular area of approximately 2.6 optic disc radii surrounding the center of optic disc was cropped. The non-vessels fragments were removed. FracLac was used to measure the fractal dimension and vessel density of retinal vessels. Results: This study suggested that 14.1% of the region of interest (i.e. approximately 2.6 optic disk radii) comprised retinal vessel structure. Using correlation analysis, vessel density measurement and fractal dimension estimation are linearly and strongly correlated (R = 0.942, R2 = 0.89, p50.001). Polynomial regression model suggests quadratic regression as the best fit for our data (linear: R2 = 0.1024, 198 d.f., p50.001, quadratic: R2 = 0.1236, 197 d.f., p50.001, cubic: R2 = 0.1236, 196 d.f., p50.001). Conclusions: This study demonstrated the ability of vessel density measurement to detect the changes in the morphology of retinal microvascular associated with increasing age. Thus, vessel density can be suggested to be another parameter in the quantification of retinal microvasculature